Narrating from landscape in Andean archaeology: The problem with the suni natural region. (June 2022) - Ramón, Gabriel; Bell, Martha G
Archaeologists use the landscape to explain the past, often referring to traditional or indigenous knowledge to better understand that landscape. But how is this analogical process performed, and how is indigenous knowledge understood and recorded? This article examines Peruvian geographer Javier Pulgar Vidal's concept of suni —a term with several definitions in Aymara and Quechua, but which was transformed by Pulgar Vidal into a "Natural Region, " in other words a meaningful portion of the landscape—as an entry point into this broader issue. Suni is important because it is a poorly defined part of a wider Andean landscape model supposedly based on indigenous knowledge and because it is commonly used by archaeologists to explain precolonial land use and landscapes. Through analysis of the creation and application of suni, we define major challenges faced by archaeologists when interpreting sites and materials in landscape perspective and present suggestions for moving forward.